2021
DOI: 10.3390/nano11123381
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable, Antibacterial, Isoporous Through-Hole Membrane Air Filters with Hydrothermally Grown ZnO Nanorods

Abstract: Reusable, antibacterial, and photocatalytic isoporous through-hole air filtration membranes have been demonstrated based on hydrothermally grown ZnO nanorods (NRs). High-temperature (300~375 °C) stability of thermoset-based isoporous through-hole membranes has enabled concurrent control of porosity and seed formation via high-temperature annealing of the membranes. The following hydrothermal growth has led to densely populated ZnO NRs on both the membrane surface and pore sidewall. Thanks to the nanofibrous sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…There are studies on the synthesis of ZnO nanorods (ZnO NRs) porous membrane by hydrothermal method. Due to the fibrous nature of ZnO NRs, it shows very good filtration performance, and it endows the membrane with antibacterial and photocatalytic activities, and it is found that Gram-positive bacteria and Staphylococcus aureus are killed on the ZnO NRs porous membrane (Choi et al, 2021).…”
Section: Application Of Zno Nmts In Bacteria and Its Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies on the synthesis of ZnO nanorods (ZnO NRs) porous membrane by hydrothermal method. Due to the fibrous nature of ZnO NRs, it shows very good filtration performance, and it endows the membrane with antibacterial and photocatalytic activities, and it is found that Gram-positive bacteria and Staphylococcus aureus are killed on the ZnO NRs porous membrane (Choi et al, 2021).…”
Section: Application Of Zno Nmts In Bacteria and Its Mechanismmentioning
confidence: 99%
“…As bacteria can be transferred through a wet mask, it is extremely important to improve the antibacterial ability of the mask in order to prevent cross infection or secondary infection during use. According to research, NPs can be used as effective antibacterial agents in wound care, and nanotechnology has the potential to fundamentally change the form and efficacy of traditional respiratory protection systems, contributing to improving the quality of life (Choi et al, 2021).…”
mentioning
confidence: 99%
“…Zinc oxide (ZnO) NPs, in particular, are extensively studied for their antibacterial potential and skin-friendly properties [19]. They have been integrated into various applications, such as air filters with antibacterial properties [20], antibacterial cotton materials for healthcare applications [21,22], textiles with photocatalytic self-cleaning and UV protection [23], and wound dressings [24]. ZnO NPs, synthesized through various methods, exhibit multiple activities, including antibacterial, antiviral, antifungal, antioxidant, anticancer, anti-inflammatory, wound healing, antidiabetic, and cardioprotective effects [25].…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al. [ 6 ] and his research team analyzed nanoparticles as efficient antibacterial agents for wound care. The field of nanotechnology holds promise in revolutionizing the structure and effectiveness of conventional respiratory protection systems, thereby enhancing overall quality of life.…”
Section: Introductionmentioning
confidence: 99%